Sex-biased suppression of chemically induced neural carcinogenesis in congenic BDIX.BDIV-Mss4a rats - Kölsch, Bernd; Winzen-Reichert, Bettina; Fischer, Christine; Kutritz, Andrea; van den Berg, Linda; Kindler-Röhrborn, Andrea (Physiological genomics, 2011)
We previously mapped several gene loci influencing cancer risk of inbred BDIV and BDIX rats, resistant and susceptible, respectively, to N-ethyl-N-nitrosourea (ENU)-induced malignant peripheral nerve sheath tumors (MPNSTs). On the basis of a genomewide association analysis using a (BDIV × BDIX) F2 generation the Mss4 locus on rat chromosome 6 was predicted to mediate resistance to MPNST development in the trigeminal nerves, preferentially in females. F2 females homozygous for D6Mit1 proved almost exclusively resistant to peripheral neurooncogenesis, with no effect detectable in males. To functionally verify Mss4, a congenic BDIX rat strain was generated carrying a corresponding BDIV genomic fragment. On treatment with ENU, congenic BDIX.BDIV-Mss4a rats showed a 2.4-fold lower MPNST rate and a 55-day-longer survival time compared with BDIX animals. The sex-specific effect observed in F2 rats was less pronounced in BDIX.BDIV-Mss4a congenics, with males, too, being protected against MPNST but to a lesser extent than females. Transcription profiling using trigeminal nerve tissue of BDIX, BDIV, and BDIX.BDIV-Mss4a congenics of both sexes revealed 61 genes located in the Mss4a fragment differentially expressed between BDIV and BDIX rats. In congenic rats each gene either displayed trans-regulated BDIX-like expression strength or cis-regulated BDIV-like transcript levels or intermediate expression without marked sex differences. Genomewide a number of genes exhibiting male-biased expression in the BDIX rat strain displayed a reversal of the sexual dimorphism in congenic rats similar to the BDIV expression pattern, which might be the basis of preferential protection of females against MPNST development.
Gesehen am 06.07.2022